Mesoporous Thin-Wall Molybdenum Nitride for Fast and Stable Na/Li Storage - Jiang, Guangshen; Qiu, Yuqian; Lu, Qingqiong; Zhuang, Wanqi; Xu, Xiaosa; Kaskel, Stefan; Xu, Fei; Wang, Hongqiang (ACS Applied Materials and Interfaces, 2019)
Sluggish reaction kinetics induced by the poor solid-state ion diffusion and low electrical conductivity of electrode materials are currently in conflict with increasing fast-charge needs for sodium-ion batteries (SIBs) based on conversion mechanism. Herein, mesoporous, conductive, thin-wall three-dimensional (3D) skeletons of molybdenum nitride (meso-Mo2N) were established and employed as anodes to facilitate the rate performance of SIBs. Mesoporous channels (∼9.3 nm) with very thin walls (<8 nm) and conductive networks in meso-Mo2N enable the rapid Na+ infiltrability/diffusion and fast electron migration, respectively. The facilitated ion diffusion/transfer ability is corroborated by cyclic voltammetry tests and galvanostatic intermittent titration technique with a higher Na+ diffusion coefficient and a larger Na+ diffusion-dominated capacity. Consequently, meso-Mo2N exhibits a superior rate capability and a steady specific capacity of 158 mAh g-1 at 1 A g-1 after 1000 cycles for SIBs, surpassing the nonporous Mo2N and even the previously reported Mo2N. Furthermore, the proof of concept can be also extended to enhanced Li storage. Such a mesostructured design with 3D mesoporous, conductive thin walls of electrodes is a promising strategy for achieving fast-charging and high-performance Na/Li storage.
CRIS-Team Scopus Importer:2022-04-14
Keywords: fast charging; lithium-ion batteries; molybdenum nitride; sodium-ion batteries; thin wall